Corporate social responsibility communication for both business and societal sustainability in ten South African organisations - Louise Bezuidenhout; Elbe Kloppers (Communicare)
In the context of South Africa as a developing country, we argue that CSR communication should contribute to both business sustainability and the empowerment of society for societal sustainability. This study aimed to explore the perceptions of senior South African communication practitioners regarding sustainability and the practice of CSR communication to support dual sustainability. Semi-structured interviews were conducted with ten senior communication practitioners responsible for CSR and/or CSR communication in ten national and international organisations across South Africa. Our findings revealed that although all practitioners recognised sustainability as the purpose of CSR, business sustainability was prioritised, while societal sustainability has only been supported. CSR communication was primarily used to enhance business sustainability by portraying the company as a responsible corporate citizen through corporate communication efforts to enhance its reputation. This is attributed to the fact that the current CSR communication theory is based on corporate communication, which prioritises business objectives. We contend that a more comprehensive theoretical framework, including principles of development communication, would enable CSR communication to significantly contribute to societal sustainability.